2012
DOI: 10.1534/g3.112.002311
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Ascites Resistance and Tolerance in Chicken: A Random Regression Approach

Abstract: Resistance and tolerance are two complementary mechanisms to reduce the detrimental effects of parasites, pathogens, and production diseases on host performance. Using body weight and ascites data on domesticated chicken Gallus gallus domesticus, we demonstrate the use of random regression animal model and covariance functions to estimate genetic parameters for ascites resistance and tolerance and illustrate the way individual variation in resistance and tolerance induce both genotype re-ranking and changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 65 publications
3
28
0
Order By: Relevance
“…Closter et al (2012) reported that the genetic correlations between body weight and the proportion of the heart decreased with a signal change as the age of the chickens increased (0.11± 0.12, -0.09 ± 0.13, and -0.43 ± 0.11 for live weights at 14, 35, and 49 days of age relative to the proportion of the heart, respectively). A similar trend was observed by Kause et al (2012), who found genetic correlation estimates of 0.12 ± 0.12 between live weight at 14 days of age and the proportion of the heart, and -0.33 ± 0.12 between live weight at 49 days of age and the proportion of the heart.…”
Section: Resultssupporting
confidence: 87%
“…Closter et al (2012) reported that the genetic correlations between body weight and the proportion of the heart decreased with a signal change as the age of the chickens increased (0.11± 0.12, -0.09 ± 0.13, and -0.43 ± 0.11 for live weights at 14, 35, and 49 days of age relative to the proportion of the heart, respectively). A similar trend was observed by Kause et al (2012), who found genetic correlation estimates of 0.12 ± 0.12 between live weight at 14 days of age and the proportion of the heart, and -0.33 ± 0.12 between live weight at 49 days of age and the proportion of the heart.…”
Section: Resultssupporting
confidence: 87%
“…Studies indicating higher heritability values of resistance (i.e. greater than 20%) have generally been conducted in experimental settings [47,48] whereby non-transmitted factors were controlled for. It is hence likely that our relatively low values of heritability are inherent to the natural settings in which we performed our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, models that are able to accommodate this feature are essentially useful for the modern poultry breeding. The RNM have been generally used to study G×E interaction for disease resistance in other species, such as chicken (Kause et al, 2012), dairy (Calus et al, 2006) and beef (Mota et al, 2016) cattle. However, to our knowledge, studies on trait growth performance under different nutritional levels are still scarce, mainly for meat quail.…”
Section: Introductionmentioning
confidence: 99%